2019
DOI: 10.1371/journal.pmed.1002835
|View full text |Cite
|
Sign up to set email alerts
|

Biannual mass azithromycin distributions and malaria parasitemia in pre-school children in Niger: A cluster-randomized, placebo-controlled trial

Abstract: Background Mass azithromycin distributions have been shown to reduce mortality in preschool children, although the factors mediating this mortality reduction are not clear. This study was performed to determine whether mass distribution of azithromycin, which has modest antimalarial activity, reduces the community burden of malaria. Methods and findings In a cluster-randomized trial conducted from 23 November 2014 until 31 July 2017, 30 rural communities in Niger were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 22 publications
0
51
2
Order By: Relevance
“… 4 6 , 37 Recent assessment from the MORDOR trial in Niger indicated reduced malaria parasitemia in azithromycin-treated communities. 38 However, morbidity assessments as part of the MORDOR trial in Tanzania indicated no difference in fever or anemia between azithromycin and placebo arms. 39 A study comparing seasonal malaria chemoprevention (SMC) to SMC plus azithromycin in Burkina Faso and Mali, which have lower year-round malaria transmission than Malawi, reported no difference in mortality between groups, although reductions were evident in morbidity due to gastrointestinal and respiratory infections and nonmalarial febrile illness with the addition of azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“… 4 6 , 37 Recent assessment from the MORDOR trial in Niger indicated reduced malaria parasitemia in azithromycin-treated communities. 38 However, morbidity assessments as part of the MORDOR trial in Tanzania indicated no difference in fever or anemia between azithromycin and placebo arms. 39 A study comparing seasonal malaria chemoprevention (SMC) to SMC plus azithromycin in Burkina Faso and Mali, which have lower year-round malaria transmission than Malawi, reported no difference in mortality between groups, although reductions were evident in morbidity due to gastrointestinal and respiratory infections and nonmalarial febrile illness with the addition of azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Study Design: An ancillary cluster-randomized trial was initiated in the MORDOR study area of Niger in November 2013, concurrent with the main MORDOR trial. 8 A group of 30 communities was randomly selected from the larger pool of communities in the main MORDOR trial and randomized in a 1:1 ratio to the same interventions implemented in MORDOR: biannual mass treatment of 1-59 month-old children with either azithromycin or placebo. Changes in antibiotic resistance determinants were the prespecified outcomes, assessed at annual monitoring visits.…”
Section: Methodsmentioning
confidence: 99%
“…This study found no statistically significant difference in the incidence of ADRs between azithromycin as MDA and placebo (RR 0.86, 95% CI 0.68 to 1.10, P = 0.23)[32,33]. A pilot cohort study in Ghana reported that 45 out of 14,548 children (0.3%) in azithromycin as MDA had mild to moderate self-limiting ADRs including abdominal discomfort, nausea, and vomiting reported by trained volunteers[34].…”
mentioning
confidence: 67%